2017
DOI: 10.7324/japs.2017.71108
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the antioxidant and immunomodulatory properties of curcumin conjugated gold nanospheres and free curcumin

Abstract: Curcumin, a phenolic compound isolated from the rhizomes of the plant Curcuma longa, has been known for decades. Owing to the fact of its hydrophobic nature and rapid metabolization, it has not been used as an effective drug so far. To solve the problem of bioavailability of curcumin, gold nanoparticles (cAuNps) reduced and stabilized with curcumin have been prepared. Afterwards, study for their antioxidant defenses and its effect on oxidative stress has been implemented. Cell cytotoxicity of both cAuNps (2.91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…This is because gold particle also has antioxidant activity. A higher cAuNPs antioxidant activity was also shown by Singh et al [31] by using different assays, i.e., superoxide dismutase and catalase assays. While Shaabani et al [19] showed that the antioxidant activity of cAuNPs was higher than the gold nanoparticles synthesized by using sodium borohydride as reducing agent.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This is because gold particle also has antioxidant activity. A higher cAuNPs antioxidant activity was also shown by Singh et al [31] by using different assays, i.e., superoxide dismutase and catalase assays. While Shaabani et al [19] showed that the antioxidant activity of cAuNPs was higher than the gold nanoparticles synthesized by using sodium borohydride as reducing agent.…”
Section: Discussionsupporting
confidence: 55%
“…Although the successful conjugation and biological activity of cAuNPs has been shown in several studies, there is no study yet showing their effect on fibrosis. Besides, all of the toxicity studies on cAuNPs were conducted at the cellular level, which might not relate with its in vivo effect [19,24,[29][30][31]. In this study, we perform an in ovo toxicity test of cAuNPs.…”
Section: Introductionmentioning
confidence: 99%